Improving lift safety by using digital technologies - A. A. Korotkiy; V. P. Kolganov (Безопасность техногенных и природных систем, 2019)
The paper deals with the organization of the dispatching of elevators, as one of the important conditions for ensuring security, and monitoring the technical condition of elevator facilities through the use of digital technologies. This method allows to increase the safety of the operation of elevators, to ensure the operational control of the state of the elevator structures both by the operating organization and by the regulatory authorities, and to reduce the negative impact on the safety of the human factor.